Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure! Let's solve the quadratic equation [tex]\(x^2 - 3x + 7 = 0\)[/tex] using the quadratic formula. The standard form of a quadratic equation is [tex]\(ax^2 + bx + c = 0\)[/tex], where [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are constants.
In this equation, we can identify:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = -3\)[/tex]
- [tex]\(c = 7\)[/tex]
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
### Step-by-Step Solution
1. Calculate the Discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
Plugging in the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \text{Discriminant} = (-3)^2 - 4(1)(7) = 9 - 28 = -19 \][/tex]
2. Evaluate the Roots Using the Quadratic Formula:
Since the discriminant is negative ([tex]\(-19\)[/tex]), this means we will have complex (imaginary) roots.
Plugging in the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and the discriminant into the quadratic formula:
[tex]\[ x = \frac{-(-3) \pm \sqrt{-19}}{2(1)} \][/tex]
Simplify:
[tex]\[ x = \frac{3 \pm \sqrt{-19}}{2} \][/tex]
3. Express the Square Root of the Negative Discriminant:
Recall that [tex]\(\sqrt{-19} = i\sqrt{19}\)[/tex], where [tex]\(i\)[/tex] is the imaginary unit.
Thus:
[tex]\[ x = \frac{3 \pm i\sqrt{19}}{2} \][/tex]
Finally, we can write the two solutions as:
[tex]\[ x = \frac{3 + i\sqrt{19}}{2} \quad \text{or} \quad x = \frac{3 - i\sqrt{19}}{2} \][/tex]
So, the solutions to the quadratic equation [tex]\(x^2 - 3x + 7 = 0\)[/tex] are:
[tex]\[ x = \frac{3 + i\sqrt{19}}{2} \quad \text{and} \quad x = \frac{3 - i\sqrt{19}}{2} \][/tex]
In this equation, we can identify:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = -3\)[/tex]
- [tex]\(c = 7\)[/tex]
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
### Step-by-Step Solution
1. Calculate the Discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
Plugging in the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \text{Discriminant} = (-3)^2 - 4(1)(7) = 9 - 28 = -19 \][/tex]
2. Evaluate the Roots Using the Quadratic Formula:
Since the discriminant is negative ([tex]\(-19\)[/tex]), this means we will have complex (imaginary) roots.
Plugging in the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and the discriminant into the quadratic formula:
[tex]\[ x = \frac{-(-3) \pm \sqrt{-19}}{2(1)} \][/tex]
Simplify:
[tex]\[ x = \frac{3 \pm \sqrt{-19}}{2} \][/tex]
3. Express the Square Root of the Negative Discriminant:
Recall that [tex]\(\sqrt{-19} = i\sqrt{19}\)[/tex], where [tex]\(i\)[/tex] is the imaginary unit.
Thus:
[tex]\[ x = \frac{3 \pm i\sqrt{19}}{2} \][/tex]
Finally, we can write the two solutions as:
[tex]\[ x = \frac{3 + i\sqrt{19}}{2} \quad \text{or} \quad x = \frac{3 - i\sqrt{19}}{2} \][/tex]
So, the solutions to the quadratic equation [tex]\(x^2 - 3x + 7 = 0\)[/tex] are:
[tex]\[ x = \frac{3 + i\sqrt{19}}{2} \quad \text{and} \quad x = \frac{3 - i\sqrt{19}}{2} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.